2004
DOI: 10.1017/s095283690300445x
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns and home range of Cape clawless otters (Aonyx capensis), affected by high food density patches

Abstract: To determine the effects of their movement patterns, seven Cape clawless otters Aonyx capensis were caught in two rivers and radio-tracked between 1993 and 1995. Total range length varied from 4.9 to 54.1 km and core length from 0.2 to 9.8 km. Total area of water used varied between 4.9 and 1062.5 ha, and core areas from 1.1 to 138.9 ha. As predicted using the resource dispersion hypothesis, total home-range length was correlated with mean reed bed (high food density patch) nearest neighbour distance. The patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Studies have shown that male European polecats Mustela putorius and American mink use up to 3 times larger home ranges than females (Gerell 1970, Lodé 1996, Zschille et al 2006, and male pine martens Martes martes establish larger home ranges (Schröpfer et al 1997, Zalewski & Jedrzejewski 2006. Similarly, Somers & Nel (2004) reported significant differences in home range size of males and females for the African clawless otter Aonyx capensis. In the present study, male European mink home ranges were twice the size those of females, comparable to the results of Palazón & Ruíz-Olmo (1998) and Macdonald et al (2002) for Mustela lutreola and to results for Mustela nivalis and Mustela erminea, the smaller members of the Mustelid family (King 1975, Erlinge 1977, Macdonald et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that male European polecats Mustela putorius and American mink use up to 3 times larger home ranges than females (Gerell 1970, Lodé 1996, Zschille et al 2006, and male pine martens Martes martes establish larger home ranges (Schröpfer et al 1997, Zalewski & Jedrzejewski 2006. Similarly, Somers & Nel (2004) reported significant differences in home range size of males and females for the African clawless otter Aonyx capensis. In the present study, male European mink home ranges were twice the size those of females, comparable to the results of Palazón & Ruíz-Olmo (1998) and Macdonald et al (2002) for Mustela lutreola and to results for Mustela nivalis and Mustela erminea, the smaller members of the Mustelid family (King 1975, Erlinge 1977, Macdonald et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As many tourists are willing to pay R50.00 or more to view otters, a steady income for at least one trained guide at each suitable reserve along the Wild Coast (and perhaps elsewhere) is attainable. This would involve ca three hours of work in the early morning to catch the ca 2.6 hours of otter activity (Somers & Nel 2004). Seeing otters during the nocturnal activity bout is not considered feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In marine habitats they eat mostly fish followed first by crabs, then by octopus or lobster (Van der Zee 1979, 1981Arden-Clarke 1983;Verwoerd 1987;Somers 2000a, b). Cape clawless otters are typically active from dawn for 2.6 h and from sunset for a mean of 2.3 h (Somers & Nel 2004). During the heat of the day they rest in dry places, in holes in the ground, under rocks, in sheltered places in erosion gullies or in dense reed beds adjacent to their habitat (Somers 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations